Implementation of STEM Local Context in Indonesia - Elly Herliani; Lukman Nulhakim; Septian Karyana (SEAMEO QITEP in Science, 2021)
This study aims to analyze the ability of teachers in implementing Local Context STEM learning in the classroom. This research used a qualitative design and a multi case study method of the implementation of STEM learning for elementary, junior high and high school teachers in several cities in Indonesia who participated in the STEM Local Context training. Data were collected through learning observations and interviews as triangulation. The results showed 1) the teacher was able to identify local issues for STEM learning; 2) Engineering Design Process (EDP) as one of the characteristics of STEM learning that can integrate concepts to solve local issues has been illustrated in the lesson plans, 3) teachers are relatively able to implement STEM learning according to the lesson plans; 4) the teacher facilitates students so that they are able to carry out EDP relatively independently; 5) generally the products development is done in the form of homework which is monitored via WhatsApp as a solution to time constraints and other technical aspects that are not easy to do at school; 6) products resulting from STEM learning are varied and reflect local issue-based innovations; 7) get a positive response from students and improve their ability to solve problems; 8) teachers receive good support from school principals and peers in the form of permission to adjust learning schedules and technical support during the implementation of STEM learning.